Derecho administrativo colombiano: Apuntes y reflexiones contemporáneas para una pedagogía prospectiva del derecho - Riveros Vásquez, Steffani Paola (Corporación Universitaria Americana, 2021)
The book Colombian Administrative Law is an academic support for the university and research community, which was developed with the objective of strengthening knowledge, learning common pedagogical strategies in the teaching of public law, identifying topics that present learning difficulties and developing optional methods to assist the teaching process. It was developed by teachers and lawyers specialized in the area of administrative law who are also part of the research groups DehJüs and Law & Science of the Faculty of Humanities and Social Sciences of the Corporación Universitaria Americana.